Implementasi Algoritma Regresi Linear untuk Memprediksi Harga Emas - Salsabilah, Andini Fitriyah; Hanafi, Achmad Arbi; Nurilhaq, Muhammad Sabili; Wira, Putra Dwi (Fakultas Teknik dan Informatika Universitas Panca Marga, 2024)
This study aims to predict gold prices using several independent variables, including the silver exchange rate (SLV), the S&P 500 index (SPX), the United States Oil Fund (USO) stock exchange rate, and the Euro (EUR) to United States dollar (USD) exchange rate. The data used in this study is secondary data sourced from